KNOWLEDGE, ATTITUDES, AND PRACTICES OF HEALTH WORKERS TOWARDS NOSOCOMIAL INFECTION PREVENTION AT NSAMBYA POLICE HEALTH CENTRE IV, KAMPALA DISTRICT. A CROSS-SECTIONAL STUDY. - Asasiira, Phiona; Nasereko, Hasifa; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2023)
Introduction: Purpose of the study: The study aimed to determine the study knowledge, attitude, and practice of health workers toward nosocomial infection prevention at Nsambya Police Health Centre IV, Kampala District. Methodology: The study was descriptive and cross-sectional in design, employing quantitative data collection methods where an interviewer-guided semi-structured questionnaire was used as a data collection tool. The study included 50 respondents who were adolescents living in Nsambya parish, Kampala District. Data was analyzed electronically by the use of Microsoft Word Excel version 2013. Results of Study: The study showed results that 84, % of HCWs knew that the use of PPEs decreases the risk of Nosocomial infection. The study found that there are insufficient PPEs in the hospital hence affecting the good practices towards infection prevention by HCWs. Conclusion: Therefore, monitoring the level of knowledge in infection prevention will help to work on the gaps so that the rate of HAIs can be reduced. Recommendation: The government should provide Nsambya Police Health Centre IV with the requirements or equipment required in the prevention of hospital-acquired infections for example personal protective equipment for the health care workers.